Psychotic Disorders in Adolescence and Later Long-term Exclusion From Education and Employment - Ringbom Ida; Suvisaari Jaana; Kääriälä Antti; Sourander Andre; Gissler Mika; Kelleher Ian; Gyllenberg David (Oxford academic, 2022)
Background and hypothesis
Psychotic disorders have been associated with not being in education, employment, and training (NEET). There is a lack of knowledge on the importance of risk markers for NEET among people with psychotic disorders and what rehabilitation they receive.
Study design
We based our research on the register-based 1987 Finnish Birth Cohort study, which included all live births in Finland during that year. The study cohort were 288 people who had been diagnosed with psychotic disorders during 2004–2007, when they were 16–20 year old, and 55 883 who had not. We looked at the national register data for those subjects in 2008–2015, when they were 20–28 year old, and compared any associations between sociodemographic factors and NEET status.
Study results
NEET for more than 5 year affected 2.2% of those without psychosis, 35.8% of those with any nonaffective psychotic disorder, and 57.0% of those with schizophrenia or schizoaffective disorders. Family-related risk factors were weaker predictors of long-term NEET in subjects with psychotic disorders than other cohort members. Having a psychotic disorder plus long-term NEET was associated with not applying for upper secondary education, not finishing upper secondary education, parents receiving welfare benefits, being diagnosed with schizophrenia or schizoaffective disorders and being hospitalized for psychosis. Only 24.3% with psychotic disorders had participated in vocational rehabilitation.
Conclusions
A diagnosis of psychosis in adolescence is independently associated with serious long term functional disability. Among those with psychotic disorders, educational problems are markers for adverse labor market outcomes. Despite this, vocational rehabilitation is seldom provided.